Small Nucleolar RNA Host Gene 18 Acts as a Tumor Suppressor and a Diagnostic Indicator in Hepatocellular Carcinoma. (20th August 2018) - Liu, Xue-Fang; Thin, Khaing Zar; Ming, Xin-Liang; Shuo-Li,; Ping-Luo,; Man-Zhu,; Li, Nan-Di; Tu, Jian-Cheng
Background: Noncoding RNAs are crucial regulators acting as either tumor suppressor genes or oncogenes in human cancer progression. The aberrant expression of noncoding RNAs has been confirmed in different kinds of cancers. Hepatocellular carcinoma is one of the most common malignant tumors worldwide, characterized by insidious onset, great malignancy, and high rates of recurrence and metastasis. Due to lack of early predictive markers, numerous patients are diagnosed in the late stages. As therapeutic options for advanced patients are quite limited, great efforts have been made to screen patients at early stages. A previous study reported that small nucleolar RNA host gene 18 played crucial role in glioma. However, its functions and roles in hepatocellular carcinoma are unknown. Purpose: To explore its functional role and diagnostic value in hepatocellular carcinoma, we investigated its expression level. Methods: We performed real-time quantitative polymerase chain reaction in tumor tissues and adjacent noncancerous tissues derived from patients with hepatocellular carcinoma as well as in plasma, including samples from the healthy control, patients with hepatitis B, cirrhosis, and hepatocellular carcinoma. Results: Small nucleolar RNA host gene 18 was downregulated in liver tissues compared to paired adjacent noncancerous tissues ( P < .0001). Meanwhile, plasma small nucleolar RNA host gene 18 showed a relatively high sensitivity and specificity (75.61% and 73.49%) for distinguishing patients with hepatocellular carcinoma whose α-fetoprotein levels were below 200 ng/mL from the healthy controls. Conclusion: Our study suggested that small nucleolar RNA host gene 18 might act as a tumor suppressor gene in hepatocellular carcinoma and potentially a diagnostic indicator to distinguish hepatocellular carcinoma from the healthy control and cirrhosis.